MAGIC observations of the microquasar V404 Cygni during the 2015 outburst. Issue 2 (8th July 2017) - Ahnen, M. L.; Ansoldi, S.; Antonelli, L. A.; Arcaro, C.; Babić, A.; Banerjee, B.; Bangale, P.; Barres de Almeida, U.; Barrio, J. A.; Becerra González, J.; Bednarek, W.; Bernardini, E.; et al.
Abstract: The microquasar V404 Cygni underwent a series of outbursts in 2015, June 15–31, during which its flux in hard X-rays (20–40 keV) reached about 40 times the Crab nebula flux. Because of the exceptional interest of the flaring activity from this source, observations at several wavelengths were conducted. The MAGIC telescopes, triggered by the INTEGRAL alerts, followed-up the flaring source for several nights during the period June 18–27, for more than 10 h. One hour of observation was simultaneously conducted on a giant 22 GHz radio flare and a hint of signal at GeV energies seen by Fermi -LAT. The MAGIC observations did not show significant emission in any of the analysed time intervals. The derived flux upper limit, in the energy range 200–1250 GeV, is 4.8 × 10 −12 photons cm −2 s −1 . We estimate the gamma-ray opacity during the flaring period, which along with our non-detection points to an inefficient acceleration in the V404 Cyg jets if a very high energy emitter is located further than 1 × 10 10 cm from the compact object.